POLA PENYIKAPAN TERHADAP PENYAKIT MENULAR DAN WABAH BERDASARKAN PERSPEKTIF FIQH DALAM ISLAM - Muhammad Mahmud (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2020)
The phenomenon of the corona virus outbreak (covid-19) that emerged in early 2020 is increasingly making concern around the world. How not, the virus that first appeared in the city of Wuhan in China's Hubei province has claimed more than 2600 lives and infected about 80,000 people or more.Lifestyle related to health according to the Islamic view has developed rapidly and followed the times and is the result of the connection of the Qur'an to health. Nowadays there are infectious diseases or epidemics all over the world such as Covid Virus 19. Responding to this global epidemic, as a Muslim, you should return to the teachings of Islam contained in the Qur'an and Hadith.